Chapter 2 Viking camps: A historiographical overview - Williams, Gareth (Taylor & Francis, 2023)
This paper presents a broad-reaching overview of the study of Viking camps, and how this has developed since the 1970s. The paper considers how the camps have been interpreted in the past, summarises the evidence of the individual sites which have been investigated, and draws out a number of key themes which have emerged in recent research on the subject, both in this volume and elsewhere.